Mechanical properties and degradation of porous magnesium for cancellous bone subsitution [electronic resource] - Mohd Faidzul Awwal Ahmad Fadzir, 1987-; Ardiyanshah Syahrom, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia,2014